2023
DOI: 10.35870/jimik.v4i1.149
|View full text |Cite
|
Sign up to set email alerts
|

Analisa Performa Algoritma Machine Learning Dalam Prediksi Penyakit Liver

Abstract: Currently in the world of medicine, determining liver inflammation is something that is not easy to do. But there are medical records that have kept the patient's symptoms and diagnosis of liver inflammation. The weaknesses of the manual method encourage researchers to develop a method that does not depend 100% on humans. The developed method utilizes a computer as a tool to analyze data. This kind of thing is certainly very useful for health experts. They can use existing medical records as an aid in making d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
1
0
3
Order By: Relevance
“…It demonstrated that the C4.5 AdaBoost method outperformed other algorithms in terms of accuracy, achieving a rate of 77.12% [6]. Additionally, in a study analyzing the performance of machine learning algorithms in liver disease prediction, the C4.5 algorithm achieved an accuracy of 70.29%, while the Naïve Bayes algorithm achieved an accuracy of 67.05% [7]. Moreover, a study on heart disease classification examined the effectiveness of the C4.5 algorithm with feature selection and subsequent application of the AdaBoost ensemble, which improved the accuracy by 10.33% in diagnosing heart disease [8].…”
Section: Introductionmentioning
confidence: 95%
“…It demonstrated that the C4.5 AdaBoost method outperformed other algorithms in terms of accuracy, achieving a rate of 77.12% [6]. Additionally, in a study analyzing the performance of machine learning algorithms in liver disease prediction, the C4.5 algorithm achieved an accuracy of 70.29%, while the Naïve Bayes algorithm achieved an accuracy of 67.05% [7]. Moreover, a study on heart disease classification examined the effectiveness of the C4.5 algorithm with feature selection and subsequent application of the AdaBoost ensemble, which improved the accuracy by 10.33% in diagnosing heart disease [8].…”
Section: Introductionmentioning
confidence: 95%
“…Data yang belum melalui proses preprocessing data input Menurut Nurkholifah, Jasmarizal, Yusron Umar dan Rahmaddeni preprocessing didefinisikan sebagai berikut Prepocessing adalah tahap awal sebelum melakukan pengujian algoritma, dimana data yang yang digunakan diolah menjadi data bersih siap uji. Prepocessing bertujuan menghilangkan noice dan menyeragamkan bentuk data yang sesuai dengan kebutuhan model algoritma [7].…”
Section: Kebutuhan Data Inputunclassified
“…Splitting Data Setelah tahap preprocessing, langkah selanjutnya adalah membagi data menjadi data latih dan data uji. Dengan pemisahan data 60:40, 70:30, 80:20, Data yang belum pernah digunakan dalam suatu penelitian, tetapi juga berguna untuk mengevaluasi keberhasilan atau kegagalan suatu penelitian, disebut data pengujian, sedangkan data pelatihan adalah data yang digunakan untuk melakukan penelitian [12]…”
Section: 4unclassified